Alpha-gal syndrome: exploring the link between tick bites and red meat allergy - Szymonik, Julia; Szopa, Sebastian (Quality in Sport, 2024)
Introduction: Alpha-gal syndrome (AGS) arises from tick bites, triggering excessive IgE antibodies to galactose-α-1,3-galactose (α-Gal). Symptoms vary, often appearing post-α-Gal ingestion, ranging from mild to severe, including urticaria, angioedema and respiratory issues. Delayed symptom onset complicates diagnosis, posing challenges for patients. AGS can also result from contact with medical animal-derived products, such as bovine-derived heart valves, necessitating heightened healthcare provider awareness, especially in tick-exposed regions. Management involves allergen avoidance and emergency medications like epinephrine. Further research is needed to refine diagnostic and therapeutic approaches. Purpose: Through literature review and clinical presentation description, we aim to raise awareness and enhance understanding of alpha-gal syndrome. Description of the state of knowledge: AGS, an emerging atypical food allergy, stems from immune reactions to α-Gal oligosaccharide in mammalian meat and other animal products. Avoiding medical items containing alpha-gal is crucial to prevent iatrogenesis. Summary: Understanding AGS etiology and symptoms is vital for diagnosis and management. Healthcare providers’ lack of awareness may lead to underdiagnosis, inadequate patient care, and underestimation of affected individuals.